Lesson learned from the Former Yugoslavia : the case of Croatia - Čorkalo Biruški, Dinka (Array, 2012)
In this chapter dissolution and fall of the Former Yugoslavia will be presented from the socio-psychological point of view, by using examples of paradigmatic cases, like the city of Vukovar. I will argue against a widespread thesis that the bloodshed was caused by the ancient hatred that had been ostensibly prevalent among the ethnic groups and nation in the area. A process of identity construction and re-construction will be emphasized and a role of nationalistic ideology in the process will be elaborated. Examples of gradual disintegration of previously highly integrated communities will be given and the development of divided communities will be described in the context of post-war social recovery. Concepts of reconciliation versus social reconstruction will be contrasted and their similarities and differences elaborated. A role of recent trauma on individual and collective level will be considered and its implications for the post-war social reconstruction processes elaborated.